THE INTEGRATION OF SHARIA FINTECH, DIGITAL FINANCIAL LITERACY, AND CLIMATE CHANGE RISK MANAGEMENT ON SUSTAINABLE VILLAGE ECONOMIC RESILIENCE - Awwaliah,; Lestari, Soraya; Lisnawati,; Albar, Rizka (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Economic resilience is crucial to supporting the Government's SDGs goals. Sustainable economic resilience that positively impacts communities is built on village governance. The budget determines the capacity for investment in technology, where technology is a transformational tool that helps villages increase productivity and diversify their economies, such as financial technology that integrates sharia components. The urgency of this research lies in the urgent need to improve access to finance in accordance with Sharia principles for MSMEs, as well as to enhance their capacity to adapt to environmental risks. The objective of this research is to explore how this integration can be implemented to increase financial inclusion and strengthen economic resilience at the village level. The method used in this research is a qualitative approach. This research uses an interdisciplinary approach that adopts the S-O-R (Stimulus-Organism-Response) model. The research results show that Islamic fintech and climate risk influence sustainable village economic resilience. However, digital financial literacy does not contribute to sustainable village economic resilience. This is due to knowledge and understanding, not actual use. People are aware of digital financial applications but have not actively used them. Infrastructure support, trust, and real utilization are needed to achieve sustainable economic impact.